Detiction of some Virulence Factors for Staphylococcus aureus Isolated from Conjunctivitis in Numan Teaching Hospital - Othman S.muter; Laith m. najeb (مجلة جامعة الانبار للعلوم الصرفة, 2018)
The study included the collection of a sample of 80 patients reviewers for consulting eyes in Numan Teaching Hospital, the injured eye infections in patients ages ranged from (70-5) for males and females, Results showed the first examination that the 68 samples by 85 % been positive bacterial growth either samples of 12 that was negative bacterial growth accounted for 15%. the results showed the sovereignty of staphylococcus aureus by 32.05 %. varied in sensitivity assay results over the isolates under study used antibiotics response as isolates showed resistance to anti Pencillin G, Ampicillin 100% each, while the resistance to antibiotics Amoxicillin by 72% and 60% Erthromycin. While the anti Tetracycline antibiotics more influence on these isolates as percentage of their sensitivity to the anti 100%. has been investigating the viability of resistant bacteria to produce some virulence factors as it was found that all isolates were resistant to more than three antibiotics or above have the ability to produce Haemolysin enzyme, Urease enzyme, Siderophores, Gelatinase enzyme, Lipase enzyme, Capsule , β-Lactamase enzyme Production and Biofilm. While they are not able to produce the Protease enzyme.